Alpha-Mangostin Attenuates Oxidative Stress and Apoptosis in Scopolamine-Induced Amnesic Rat Brains - Suksan Changlek; Rungrudee Srisawat (Tehran University of Medical Sciences, 2022)
The extract from Garcinia mangostana L. pericarp was reported to scavenge radicals, inhibit acetylcholinesterase (AChE) activity, and improve spatial memory in scopolamine (SCOP)-induced amnesic rats. This study investigated α-mangostin (α-MG) neuroprotective effects against SCOP-induced neurotoxicity.The compound was evaluated for anti-AChE and antioxidant properties in vitro, and its preventive effect on apoptosis and oxidative stress in SCOP-treated rat brains. AChE inhibitory property of α-MG was assessed by fast blue B (FB) salt and β-naphthyl acetate (NA) and Ellman's assays. The antioxidant properties of α-MG were assessed by ferric reducing antioxidant power (FRAP), scavenging activity of 1,1-diphenyl-2-picrylhydrazyl (DPPH), and 2,2'-azino-bis-[3-ethylbenzothiazoline-6-sulfonic acid] (ABTS•+) radicals. Brain levels of malondialdehyde (MDA), lipid peroxidation marker, and activities of the caspase-3 enzyme, an apoptosis-related marker, were determined in SCOP-treated rats pretreated with donepezil (DPZ) and α-MG. IC50 of α-MG and DPZ for AChE activity were 64.23±0.22 and 32.46±0.14 mg/mL, respectively. α-MG and DPZ (100-600 µg/mL) gave FRAP values within the range of 20-410 µmol Fe2+/L. The IC50 of α-MG and DPZ for ABTS were 21.52±3.45 and 14.53±1.86 µg/mL, and for DPPH were 38.12±8.36 and 29.44±5.13 µg/mL, respectively. Prior given to SCOP-induced rats, DPZ and α-MG (50 and 100 mg/kg) reduced MDA levels, and pretreatment of DPZ and α-MG (50 mg/kg), but not α-MG (100 mg/kg), attenuated the increase of caspase-3 activity in cerebral cortex and hippocampus (P<0.05), but not in the basal forebrain. The present study is the first report of α-MG as a potential neuroprotective candidate, and its mechanism might be involved in ameliorating scopolamine-induced neurotoxicity via inhibition of lipid peroxidation and caspase-3 enzyme activity in the cerebral cortex and hippocampus.